Exploration of Thermophilic Bacteria: Systematic Literature Review - Gustina Indriati; Ruth Rize Paas Megahati S. (Jurnal Penelitian Pendidikan IPA, 2023)
The selection of enzymes derived from microbes has several advantages compared to those derived from animals and plants. One of the advantages is that the growth of enzymes will occur more quickly in bacteria because the cells rapidly undergo division and cell production will be easier to increase if needed in large quantities and the time needed for enzyme production will be shorter. Thermophilic microorganisms are known as bacteria that are tolerant of high temperatures, but on the other hand these bacteria are also able to survive at these temperatures. Where the purpose of research is to explain exploration of thermophilic bacteria. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guideline. Bacteria have important economic value in human life. Knowledge in this branch of science is useful in medicine, hygiene, food science and nutrition, agriculture, and industry. Based on the results of macroscopic, microscopic and biochemical characterization, it was found that many bacteria with various types recording to their habitat or place of development, exploraton of thermophilic bacteria was carried out so that they could be useful for the industrial world. Â